New analysis method of biomechanical curves - Kleshnev, V. (BioRow, 2023)
Do you know that female scullers exhibited the most "front-loaded" force curve, followed by male scullers. Sweep rowers, on the other hand, displayed slower catch force gradients. In the second half of the drive, male scullers demonstrated superior force maintenance, while female sweep rowers experienced an earlier drop, possibly indicating differences in upper body muscle strength among the categories.